Geographies of Academic Research on Migration and School: Voices, Silences and Prospects of Our Profession [Geografías de la Investigación Académica Sobre Migración y Escuela: Voces, Silencios y Prospectivas de Nuestra Profesión] - Aguilera-Valdivia, M (Universidad Austral de Chile, 2018)
In spite of the progressive interest in developing educational research on the schooling of immigrant students, to date there is no comprehensive review regarding what contributions we have made from the academic field to the study of the migratory phenomenon in the school environment. In this scenario and through the analysis of 32 articles, we document the academic voice on the schooling of immigrant students, which allow us to answer four key questions: 1) what is the nature of these articles? 2) what topics have been investigated? 3) what methodologies have predominated in those of an investigative nature? and finally, 4) what intercultural education approaches are based on them? The discussions aim to identify the contributions as well as the challenges facing the field in relation to the questions mentioned above. The purpose of our work is therefore to contribute to a greater self-understanding of educational research carried out in migration contexts. © 2018 Universidad Austral de Chile.